Enhanced Antitumor Efficacy and Reduced Systemic Toxicity of Sulfatide-Containing Nanoliposomal Doxorubicin in a Xenograft Model of Colorectal Cancer - Lin, Jia; Yu, Yan; Shigdar, Sarah; Fang, Ding Zhi; Du, Jun Rong; Wei, Ming Q.; Danks, Andrew; Liu, Ke; Duan, Wei (PLOS ONE, 2012)
Sulfatide is a glycosphingolipid known to interact with several extracellular matrix proteins, such as tenascin-C which is overexpressed in many types of cancer including that of the colon. In view of the limited success of chemotherapy in colorectal cancer and high toxicity of doxorubicin (DOX), a sulfatide-containing liposome (SCL) encapsulation approach was taken to overcome these barriers. This study assessed the in vitro cytotoxicity, biodistribution, therapeutic efficacy and systemic toxicity in vivo of sulfatide-containing liposomal doxorubicin (SCL-DOX) using human colonic adenocarcinoma HT-29 xenograft as the experimental model. In vitro, SCL-DOX was shown to be delivered into the nuclei and displayed prolonged retention compared with the free DOX. The use of this nanodrug delivery system to deliver DOX for treatment of tumor-bearing mice produced a much improved therapeutic efficacy in terms of tumor growth suppression and extended survival in contrast to the free drug. Furthermore, treatment of tumor-bearing mice with SCL-DOX resulted in a lower DOX uptake in the principal sites of toxicity of the free drug, namely the heart and skin, as well as reduced myelosuppression and diminished cardiotoxicity. Such natural lipid-guided nanodrug delivery systems may represent a new strategy for the development of effective anticancer chemotherapeutics targeting the tumor microenvironment for both primary tumor and micrometastases.